An exploratory study on written corrective feedback in the use of conjunctions among Malaysian ESL learners / Evon Lee Yin Cheng - Evon , Lee Yin Cheng (2017)
This study explored the extent of influence of metalinguistic corrective feedback on Malaysian ESL learners’ appropriate and inappropriate use of conjunctions and investigated the learners’ perceptions on the use of metalinguistic corrective on conjunctions use in writing practice. 30 students were recruited as samples in this mixed-method study and data were collected from three different sources: students’ essays, questionnaires and semi-structured interviews. This study obtained 90 writing assignments in the form of three essays from 30 students to explore the extent of influence of metalinguistic corrective feedback on the learners’ appropriate and inappropriate use of conjunctions. Survey questionnaire were gathered from the 30 students and subsequently six students (two high proficiency, two intermediate proficiency, and two low proficiency) were interviewed to investigate the learners’ perceptions on the use of metalinguistic corrective on conjunctions use in writing practice. The appropriate and inappropriate use of conjunctions for each category: additive conjunctions, causal conjunctions, temporal conjunctions, and adversative conjunctions were counted for three writing assignments (expository essay, cause and effect essay, and problem-solution essay). The results showed that additive conjunction was most frequently used by the learners whereas adversative conjunction was least frequently used. In addition, the results also displayed positive influence of metalinguistic corrective feedback on the ESL learners’ use of conjunctions as the percentage of appropriate use shows positive increasing trend and the percentage of inappropriate use gradually decreased for all four categories of conjunctions for each subsequent writing task. Based on the response from the survey questionnaire, the findings generally revealed positive perceptions by the ESL learners on metalinguistic corrective feedback in three main aspects: the helpfulness of coded metalinguistic corrective feedback, their feelings receiving metalinguistic corrective feedback in their writing, and their preferences on receiving feedback. Last but not least, the interview also discovered the learners’ positive perceptions on the efficacy of metalinguistic corrective feedback focusing on the feedback as mediator tool, a trigger for noticing, and a favourable correction aid for conjunctions use in writing in this study.